Cost-Effective and Rapid Detection of Tetrodotoxin Using Indium Tin Oxide Electrodes via In Vitro Electrophysiology and Electrochemistry - Pandurangi, Naga Adithya Chandra; Santafe, Manel M; Tudo, Angels; Ozsoy, Nagihan; Sureda, Fransesc X; Dallas, Mark L; Katakis, Ioanis (Toxins, 2025)
The real-time, cost-effective detection of marine toxins like tetrodotoxin (TTX) remains a significant challenge for the scientific community. Traditional methods, including cell-based assays (CBAs), high-performance liquid chromatography (HPLC), and automated patch clamp (APC), are time-consuming, requiring expensive lab-based equipment and highly trained personnel. Enzyme-linked immunosorbent assays (ELISAs), lateral flow assays (LFAs), and immunosensors may not be suitable for toxin analogues. Thus, a simplified approach has been developed in this study, which involves the electrophysiological and electrochemical interrogation of N2a cells grown on ITO-coated glass electrodes by measuring extracellular field potentials (EFP) in conjunction with whole-cell patch clamp recordings and electrochemical impedance spectroscopy (EIS) measurements both before and after incubation with TTX. The ITO substrate proved biocompatible and non-toxic for N2a cells. TTX exposure caused 102% inhibition in EFP values at 300 nM, confirmed by sodium current inhibition of 93% at 300 nM and 22% at 1 nM in patch clamp studies (IC 50 = 6.7 nM). EIS measurements indicated concentration-dependent impedance changes in the range of 6-300 nM. This research aims to provide a proof-of-concept for integration of electrophysiological and electrochemical approaches to simplify toxin detection systems.
Keywords: Tetrodotoxin/analysis; Animals; Tin Compounds/chemistry; Electrodes; Mice; Patch-Clamp Techniques; Cost-Benefit Analysis; Electrochemical Techniques/economics; Dielectric Spectroscopy; Cell Line, Tumor